Spider-Man 3 - Raimi, Sam; Ziskin, Laura; Lee, Stan 1922-; Ditko, Steve (Columbia Pictures Industries; distributed in the Philippines by MagnaVision, 2007)
Peter Parker is finally happy: he is doing well at the school, girlfriend MJ Watson loves him, and the whole city loves Spider-Man, finally bestowing upon him the praise he so rightly deserves. But peace may not be possible for a superhero. Harry Osborn has taken up his late father's mantle--becoming The New Goblin, bent on revenge. Uncle Ben's real killer, Flint Marko, has been transformed into the Sandman. An alien symbiote has attached itself to the Spider suit, turning it black, enhancing its powers, and warping Peter's personality. When Peter finally overcomes the contaminated suit, it infects rival Bugle photographer Eddie Brock, who becomes villain Venom. In this battle, Peter must conquer his personal darkness as well as Spider -Mans foes, free the compassionate hero within, and trade teenage self-absorption for adulthood.